Non-Indigenous Academic and Indigenous Autonomy - Partington, Geoffrey (The Australian Journal of Indigenous Education, 2000)
One of the many fascinating problems raised in recent issues of the Australian Journal of Indigenous Education (AJIE)is that of Indigenous autonomy in education. Although opinions differed about the extent to which Indigenous people currently exercise educational autonomy in various situations, there was wide agreement that there ought to be Indigenous control or ‘ownership’ of all knowledge relating to Indigenous life and culture, past and present. Sister Anne Gardner, then Principal of Murrupurtyanuwu Catholic School in NT, explained (1996: 20) how she decided to ‘let go, to move away from the dominant role as Principal’, in order that Indigenous persons could take control. She had been helped to this conclusion by reading Paulo Freire, Martin Buber and Hedley Beare, and, within the NT itself, ‘people of that educational calibre, such as Beth Graham, Sr Teresa Ward, Fran Murray, Stephen Harris, all pleading with us to allow education to be owned by Aboriginal people’. Sr Gardner held that ‘Aboriginal people never act as “leader”, a view shared by her designated Indigenous successor, Teresita Puruntayemeri, then Principal-in-Training of Murrupurtyanuwu Catholic School, who wrote (1996: 24-25) that ‘for a Tiwi peron it is too difficult to stand alone in leadership’. One way to share the burdens of leadership is, she suggests, to ‘perform different dances in the Milmaka ring, sometimes in pairs or in a group’.